Characteristics of Professional Liability Insurance for Doctors in Indonesia - I Putu Gde Budhi Setiawan; Mokhamad Khoirul Huda (Jurnal Dinamika Hukum, 2025)
Regulation of the Minister of Health of the Republic of Indonesia Number 755/MENKES/PER/IV/2011 concerning the Organization of Medical Committees in Hospitals in the section on credential mechanisms and granting of clinical authority for medical personnel in Hospitals in number 12 point D states that: "Doctors have Professional Indemnity Insurance ."This provision creates an obligation for hospitals or doctors to have professional liability insurance for doctors to protect their profession. This study aimed to determine the characteristics of professional liability insurance for doctors. The method used in this study is normative juridical with a statutory approach and a conceptual approach. This study indicates that professional liability insurance for doctors is included in loss insurance because what is insured is the risk of compensation for the doctor's profession carried out by the doctor in carrying out his profession. At the same time, the doctor's medical risk is not covered according to what is regulated in the policy. In addition, the characteristics of professional liability insurance for doctors are also related to the grouping of the level of risk of medical negligence in each classification of doctors. This group determines the premium and compensation paid to the doctor as compensation to the patient. Doctors use insurance claims to compensate patients if the doctor commits medical negligence and other costs.